Noise and Vibration Mitigation for Rail Transportation Systems Proceedings of the 12th International Workshop on Railway Noise, 12-16 September 2016, Terrigal, Australia (Notes on Numerical Fluid Mechanics and Multidisciplinary Design,, 2018)
This book reports on the 12th International Workshop on Railway Noise held on 12-16 September 2016 at Terrigal, Australia. It gathers peer-reviewed papers describing the latest developments in rail noise and vibration, as well as state-of-the-art reviews by distinguished experts in the field. The papers cover a broad range of rail noise topics including wheel squeal, policy, regulation and perception, wheel and rail noise, predictions, measurements and monitoring, interior noise, rail roughness, corrugation and grinding, high speed rail and aerodynamic noise, and structure-borne noise, ground-borne vibration and resilient track forms. It offers an essential reference-guide to both scientists and engineers in their daily efforts to identify, understand and solve a number of problems related to railway noise and vibration, and to achieve their ultimate goal of reducing the environmental impact of railway systems. .